Rekonstruksi Kebijakan Pengupahan Berbasis Keadilan Distributif: Telaah Normatif terhadap Perlindungan Pekerja Berupah Rendah - Atmari Atmari; Sudjai Sudjai; M Sifa Yulianis (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Wages constitute an essential instrument for worker protection and a mechanism for the distribution of welfare within industrial relations. However, wage policies in Indonesia remain largely oriented toward compliance with minimum wage standards and the pursuit of economic stability, thereby failing to fully ensure justice for low-wage workers. This study aims to analyze the normative construction of wage policy within the Indonesian labor law system, examine its limitations from the perspective of distributive justice, and formulate a reconstruction of a more equitable wage policy framework. This research employs a normative legal method using both the statute approach and the conceptual approach. Legal materials were analyzed qualitatively through a prescriptive method to develop legal arguments and policy recommendations. The findings reveal that the existing wage system is still dominated by a formalistic paradigm that regards compliance with minimum wage regulations as the primary indicator of worker protection. Such an approach has not adequately addressed the welfare concerns of low-wage workers and does not fully reflect the principles of distributive justice. Therefore, a reconstruction of wage policy is required through strengthening the orientation toward a living wage, integrating welfare indicators into wage formulation, providing affirmative protection for low-wage workers, and enhancing worker participation in policy-making processes. Such reconstruction is expected to promote a wage system that is more equitable, substantive, and welfare-oriented.